2012
DOI: 10.1007/s00280-012-2010-z
|View full text |Cite
|
Sign up to set email alerts
|

In vitro cytotoxicity, pharmacokinetics, tissue distribution, and metabolism of small-molecule protein kinase D inhibitors, kb-NB142-70 and kb-NB165-09, in mice bearing human cancer xenografts

Abstract: Purpose Protein kinase D (PKD) mediates diverse biological responses including cell growth and survival. Therefore, PKD inhibitors may have therapeutic potential. We evaluated the in vitro cytotoxicity of two PKD inhibitors, kb-NB142-70 and its methoxy analog, kb-NB165-09, and examined their in vivo efficacy and pharmacokinetics. Methods The in vitro cytotoxicities of kb-NB142-70 and kb-NB165-09 were evaluated by MTT assay against PC-3, androgen independent prostate cancer cells, and CFPAC-1 and PANC-1, panc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…As one example, kb-NB142-70, demonstrated significantly improved in vitro activity compared to the structurally related CID755673, but exhibited no antitumor activity in vivo, which is most likely due to rapid metabolism (17). Alternatively, a naphthyridine-based PKD inhibitor showed PKD inhibition and suppression of PKD-dependent downstream pathways in an in vivo rat model (35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As one example, kb-NB142-70, demonstrated significantly improved in vitro activity compared to the structurally related CID755673, but exhibited no antitumor activity in vivo, which is most likely due to rapid metabolism (17). Alternatively, a naphthyridine-based PKD inhibitor showed PKD inhibition and suppression of PKD-dependent downstream pathways in an in vivo rat model (35).…”
Section: Discussionmentioning
confidence: 99%
“…kb-NB142-70 also significantly inhibited cell proliferation, migration, and invasion. Unfortunately, kb-NB142-70 did not exhibit in vivo antitumor activity due to rapid metabolism (17). CRT0066101 is a small molecule PKD-specific inhibitor developed by investigators in the U.K., and it exhibited in vitro antitumor activity in human pancreatic cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…After the discovery of the first potent, selective, and cell-active small molecule inhibitor CID 755673 by our group [ 20 , 21 ] we directed significant efforts at improving its potency and selectivity through chemical modifications. While we developed leads with much improved potency and selectivity, such as kb-NB142-70 [ 20 , 22 ], the in vivo efficacy and applicability of this class of inhibitors remained limited [ 23 ]. A recent study utilizing targeted libraries of small organic kinase inhibitors has also identified a novel ATP-competitive 4-azaindole scaffold, and a set of pyrazolopyrimidine small molecule inhibitors with low nanomolar potency for in vitro inhibition of PKD that potently blocked prostate cancer cells proliferation and growth [ 18 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In support of our view, using several classes of structurally distinct small molecule inhibitors of PKD discovered by our group, including CID755673 and its analogs SD-208, kb-NB142-70, 1-naphthyl PP1 (1-NA-PP1), Compound 139 [128, 133136], which are all nanomolar cell-active pan-PKD inhibitors, we demonstrated that targeted inhibition of PKD by these inhibitors led to reduced proliferation, migration and invasion of prostate cancer cells. Altogether, these studies have validated PKD as a potential therapeutic target for prostate cancer.…”
Section: Pkd: a Friend Or Foe In Cancer Development And Progression?mentioning
confidence: 66%